Burden of Sensitive Skin (BoSS) Questionnaire and Current Perception Threshold: Use as Diagnostic Tools for Sensitive Skin Syndrome - Helena Polena; Marlène Chavagnac-Bonneville; Laurent Misery; Michèle Sayag (Medical Journals Sweden, 2021)
The assessment of sensitive skin syndrome, characterized by subjective unpleasant sensations, remains a challenge, since there is no international consensus on the best diagnostic tools. This study evaluated the combination of the Burden of Sensitive Skin (BoSS) questionnaire and the current perception threshold as diagnostic tools for sensitive skin syndrome, and the relationship between BoSS and the subjects' smoking status, phototype and skin type. A total of 100 women completed the BoSS questionnaire, and current perception threshold was measured on the face. The BoSS score was significantly higher in the self-reported sensitive skin group compared with the non-sensitive skin group (25.61 vs 14.05; p < 0.001), and in non-smokers vs smokers (23.00 vs 18.37; p < 0.05). In addition, the current perception threshold values were similar between the sensitive and non-sensitive groups. These results suggest that BoSS is a better diagnostic tool for sensitive skin syndrome than the current perception threshold, and that smokers less frequently have sensitive skin than do non-smokers.